2019
DOI: 10.1002/jlcr.3799
|View full text |Cite
|
Sign up to set email alerts
|

From octreotide to shorter analogues: Synthesis, radiolabeling, stability

Abstract: This study aims at analyzing complexation properties of two new short somatostatin analogues, their synthesis, radiolabeling with 44Sc, 207Bi, and 152Eu and stability in vitro. Short tetrapeptide Phe‐d‐Trp‐Lys‐Thr and pentapeptide Thz‐Phe‐d‐Trp‐Lys‐Thr were first conjugated with the DOTA macrocyclic chelator. These conjugates were radiolabeled with 44Sc, 207Bi, and 152Eu and characterized by thin‐layer chromatography (TLC) and HPLC. The radiochemical purity was measured using digital autoradiography and gamma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…DISCUSSIONDue to the promising therapeutic efficiency of Thz-containing peptides, we earlier evaluated their potential to be used as a part of a radiopharmaceutical. However, we have shown that the conditions for the effective labeling of DOTA-P1 and DOTA-P2 with 44 Sc, 90 Y, 152 Eu, and 207 Bi cations significantly differ and are not mainly defined by the hydrolytic behavior of cations 14,32. Bi 3+ is the mostF I G U R E 3Time dependence of the labeling yield of DOTA-P4 with different cations: (A) 44 Sc 3+ , (B) 90 Y 3+ , (C) 152 Eu 3+ , and (D) 207 Bi 3+ at 90 C hydrolysable among the cations studied; however, the maximum labeling yield for DOTA-P1 and DOTA-P2 was observed at pH 8.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…DISCUSSIONDue to the promising therapeutic efficiency of Thz-containing peptides, we earlier evaluated their potential to be used as a part of a radiopharmaceutical. However, we have shown that the conditions for the effective labeling of DOTA-P1 and DOTA-P2 with 44 Sc, 90 Y, 152 Eu, and 207 Bi cations significantly differ and are not mainly defined by the hydrolytic behavior of cations 14,32. Bi 3+ is the mostF I G U R E 3Time dependence of the labeling yield of DOTA-P4 with different cations: (A) 44 Sc 3+ , (B) 90 Y 3+ , (C) 152 Eu 3+ , and (D) 207 Bi 3+ at 90 C hydrolysable among the cations studied; however, the maximum labeling yield for DOTA-P1 and DOTA-P2 was observed at pH 8.…”
mentioning
confidence: 87%
“…30 For 90 Y 3+ , the optimal labeling conditions (pH 4, 0.1mM of DOTA-P4) were the same as for 90 Y-DOTA-P2. 14 Due to the high similarity of the chemical structures of DOTA-P2…”
Section: Labeling Of Dota-p4mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have synthesized chimeric molecules containing in their structure the pharmacophore sequence -Phe-D-Trp-Lys-Thr-OMe, which selectively acts on human lung adenocarcinoma (A549) (IC50(Human embryonic fibroblasts (HEF))/IC50(A-549) > 9) [7]. In addition, we studied the labeling of the conjugate described in this work with Sc 3+ , Bi 3+ and Eu 3+ cations and showed the stability of these complexes in solutions with biologically relevant ions and in bovine serum at 37 • C [8]. In this work, we attempted to study the conformation of the -DOTA-Phe-D-Trp-Lys-Thr-OMe conjugate to understand the structureactivity relationship using X-ray structural analysis (XRD) data and quantum chemistry methods.…”
Section: Introductionmentioning
confidence: 95%